HUBUNGAN IDENTITAS KELOMPOK DENGAN TRADISI PULANG KAMPUNG PADA MAHASISWA HINDU BALI FISIP UNIVERSITAS UDAYANA - Praptikasari, Ni Kadek Ayu Juwita; Zuryani, Nazrina; Punia, I Nengah (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT This research is motivated by the diversity of group identities held by Hindu comunities in Bali that are multidimensional. This indirectly has relationship with various traditions such as the tradition of returning home. Thissresearch is conducted to find outhow significant relationshippbetween identity of Balinese etnic group and the tradition of returning home that was carried out bysstudents of the Faculty of Social and Political Science at Udayana University. Thissstudy uses quantitative research method using Proportionate Stratified Random Sampling technique to 98 respondens, namely the students who are Hindus who come from rural area in Bali, migrate in Denpasar either temporarily or permanently. The results obtained from hypotheses testing by using correlation analysis technique indicate that there is moderate positive relationship between group identity and tradition of returning home, with corelation coeffcient number0,474. While influence of group identity on the frequency of returning home was found22,5%. Keywords: Correlation, Group Identity, Ethnic Bali, Hometown